A Unique Case of Penile Necrotizing Fasciitis Secondary to Spontaneous Corpus Cavernosal Abscess - N. J. Dempster; N. U. Maitra; L. McAuley; M. Brown; D. Hendry (Case Reports in Urology)
Corpus cavernosal abscess and necrotizing fasciitis occur rarely, and precipitating factors can usually be elicited with careful history and examination. Whilst both conditions share common risk factors such as diabetes mellitus, this is the first reported case of penile necrotizing fasciitis secondary to spontaneous corpus cavernosal abscess in an otherwise healthy patient. A 32-year-old man presented with 4-day history of swollen, painful penis, with ultrasound confirming corpus cavernosal abscess. Biopsies were taken and the cavity aspirated, but, despite intravenous antibiotics, he developed penile necrotizing fasciitis necessitating open cavernostomy and debridement. The overlying skin defect healed by secondary intention, but the patient experienced persistent postoperative erectile dysfunction, so he was referred for penile prosthesis insertion.